2019
DOI: 10.1021/acs.est.9b02021
|View full text |Cite
|
Sign up to set email alerts
|

Aminobacter sp. MSH1 Mineralizes the Groundwater Micropollutant 2,6-Dichlorobenzamide through a Unique Chlorobenzoate Catabolic Pathway

Abstract: 2,6-dichlorobenzamide (BAM) is a major groundwater micropollutant posing problems for drinking water treatment plants (DWTPs) that depend on groundwater intake. Aminobacter sp. MSH1 uses BAM as a sole source of carbon, nitrogen and energy and is considered a prime biocatalyst for groundwater bioremediation in DWTPs. Its use in bioremediation requires knowledge on its BAM-catabolic pathway which is currently restricted to the amidase BbdA converting BAM into 2,6-dichlorobenzoic acid (2,6-DCBA) and the mono-oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…MSH1 can completely mineralize BAM without accumulation of any metabolites (Albers et al, 2014). The degradation pathway is shown in Raes et al (2019). Previous sand filter studies analyzing for confirmed and possible BAM metabolites; 2,6dichlorobenzoic acid (2,6-DCBA), ortho-chlorobenzamide, and ortho-chlorobenzoic acid, never detected these in the effluent of filters augmented with Aminobacter sp.…”
Section: Chemical Analysis Of 26-dichlorobenzamidementioning
confidence: 94%
“…MSH1 can completely mineralize BAM without accumulation of any metabolites (Albers et al, 2014). The degradation pathway is shown in Raes et al (2019). Previous sand filter studies analyzing for confirmed and possible BAM metabolites; 2,6dichlorobenzoic acid (2,6-DCBA), ortho-chlorobenzamide, and ortho-chlorobenzoic acid, never detected these in the effluent of filters augmented with Aminobacter sp.…”
Section: Chemical Analysis Of 26-dichlorobenzamidementioning
confidence: 94%
“…15 The complete catabolic degradation pathway has recently been elucidated in detail. 20 The conversion of BAM to 2,6dichlorobenzoic acid ( of the overall process, 21 whereas further transformation of 2,6-DCBA is comparatively rapid in sand filters. 6 However, a specific challenge of using Aminobacter sp.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Catabolic genes on pBAM1 and pBAM2 enable MSH1 to mineralize the groundwater micropollutant BAM and use it as a source of carbon, nitrogen, and energy for growth. The amidase BbdA on pBAM1 transforms BAM to 2,6-dichlorobenzoic acid (DCBA) 7 which is further metabolized by a series of catabolic enzymes encoded by pBAM2 8 , 9 . As previously discussed 8 , the gene bbdI encoding the gluthatione dependent thiolytic dehalogenase responsible for removal of one of the chlorines from BAM together with bbdJ encoding gluthatione reductase, occur on pBAM2 in three consecutive, perfect repeats followed by a fourth, imperfect repeat.…”
Section: Resultsmentioning
confidence: 99%
“…The first step of BAM-mineralization involves the hydrolysis of BAM to 2,6-dichlorobenzoic acid (2,6-DCBA) by the amidase BbdA encoded on the 41 kb IncP1-β plasmid pBAM1 7 . Further catabolism of 2,6-DCBA to central metabolism intermediates involves enzymes encoded on the 54 kb repABC family plasmid pBAM2 8 , 9 . The strain mineralizes BAM at trace concentrations 6 and invades biofilms of microbial communities of rapid sand filters used in drinking water treatment plants (DWTPs) 10 .…”
Section: Introductionmentioning
confidence: 99%